Efficacy and safety of an expanded dulaglutide dose range: A phase 2, placebo-controlled trial in patients with type 2 diabetes using metformin - Frias, Juan P; Wynne, Alan G; Matyjaszek-Matuszek, Beata; Bartaskova, Dagmar; Cox, David A; Woodward, Brad; Li, Ying G; Tham, Lai S; Milicevic, Zvonko (Diabetes, obesity & metabolism, 2019)
AIMS: Dulaglutide, a once weekly GLP-1 receptor agonist, is approved at two doses (1.5 and 0.75 mg) for treatment of type 2 diabetes (T2D). Two higher doses of dulaglutide (3.0 and 4.5 mg) were evaluated for safety and efficacy to determine whether these doses warrant further study for improved control of glucose and body weight. MATERIALS AND METHODS: This 18-week, double-blind, phase 2 trial randomized 318 patients with T2D using ≥1500 mg metformin, to receive subcutaneous injection of placebo (n = 82), dulaglutide 1.5 mg (n = 81), dulaglutide 3.0 mg (n = 79) or dulaglutide 4.5 mg (n = 76). The primary objective was superiority of dulaglutide doses over placebo in reduction of HbA1c at 18 weeks. Secondary objectives included superiority of dulaglutide over placebo in change from baseline in body weight and fasting serum glucose (FSG) at 18 weeks. Investigational doses of dulaglutide were compared to the 1.5 mg dose as an exploratory objective. RESULTS: HbA1c reduction at 18 weeks was significantly greater with dulaglutide vs placebo (placebo, -0.44% ± 0.10% [-4.8 ± 1.1 mmol/mol]; dulaglutide 1.5 mg, -1.23% ± 0.10% [-13.5 ± 1.1 mmol/mol]; dulaglutide 3.0 mg, -1.31% ± 0.10% [-14.3 ± 1.1 mmol/mol]; dulaglutide 4.5 mg, -1.40% ± 0.10% [-15.3 ± 1.1 mmol/mol]; P < 0.001, each dose), as were changes in body weight (placebo, -1.6 ± 0.39 kg; dulaglutide 1.5 mg, -2.8 ± 0.39 kg; dulaglutide 3.0 mg, -3.9 ± 0.39 kg; dulaglutide 4.5 mg, -4.1 ± 0.41 kg; P < 0.001, each dose). All three dulaglutide doses significantly reduced FSG from baseline (1.5 mg, -36.2 ± 4.7 mg/dL [-2.0 ± 0.3 mmol/L]; 3.0 mg, -34.5 ± 4.5 mg/dL [-1.9 ± 0.3 mmol/L]; 4.5 mg, -38.0 ± 4.7 mg/dL [-2.1 ± 0.3 mmol/L]) vs placebo (-12.4 ± 4.5 mg/dL [-0.7 ± 0.3 mmol/L]) (P < 0.001, all). Safety profiles of the higher doses were consistent with the established safety profile for dulaglutide. Gastrointestinal events were mostly mild to moderate, and was dose-related for nausea. CONCLUSION: All three dulaglutide doses were superior to placebo in improving glycaemic control and reducing body weight in participants with T2D using metformin. The potential for doses of dulaglutide of 3.0 and 4.5 mg to provide additional glycaemic benefit and weight reduction with an acceptable safety profile, compared with the 1.5 mg dose, warrants further study in a phase 3 trial.
Keywords: senioři; dvojitá slepá metoda; Weight Loss; Double-Blind Method; krevní glukóza; dulaglutide; výsledek terapie; metformin; Drug Therapy, Combination; Middle Aged; Glycated Hemoglobin A; mužské pohlaví; Diabetes Mellitus, Type 2; Immunoglobulin Fc Fragments; Adult; diabetes mellitus 2. typu; glukagonu podobné peptidy; hypoglykemika; Blood Glucose; kombinovaná farmakoterapie; ženské pohlaví; Humans; imunoglobuliny - Fc fragmenty; hmotnostní úbytek; Glycated Hemoglobin; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; glykovaný hemoglobin; lidé středního věku; dospělí; Female; Aged; Glucagon-Like Peptides; Hypoglycemic Agents; GLP-1; Treatment Outcome; type 2 diabetes; Metformin; lidé; Male